Domain decomposition analysis of aerodynamic coupling - Aydın, Özkan. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2008., 2008)
The main objective of this research is the computational modeling and analysis of aerodynamic-coupling effects of multiple bodies in motion in a fluid using domain decomposition techniques. Simulation of such a flow field requires the solving of the nonlinear equations of the fluid motion. The computational model and techniques are first tested in the analysis of the internal flow problem. However, the objective of this thesis work is to analyze the aerodynamic coupling observed in the external flow problem. Computational domains is separated into simple cartesian subdomains. The flow at these subdomains is solved separately using stream function, vorticity formulation and these solutions are transferred into each other using the alternating multiplicative Schwarz technique. Newton’s method combined with two different Krylov sub-space solvers is applied to solve the flow problem in rectangular region. In order to have global convergence, backtracking algorithm is used within Newton method. In order to decrease computational work, local mesh refinement strategy is used in critical areas of domains. In the internal flow problem, the effects of Reynolds number on the flow are investigated for three different Reynolds numbers, namely, Re=50, Re=100, Re=150. In the external flow problem, influences of the angle-of-attack, Reynolds number, and longitudinal distance between the objects on the flow properties are investigated.|Keywords: Newton’s method, backtracking, Krylov solvers, domain decomposition, internal flow, external flow
Keywords: Newton-Raphson method.; Decomposition method.